The dissolved Beryllium isotope composition of the Arctic Ocean - Frank, M; Porcelli, D; Andersson, P; Baskaran, M; Bjork, G; Kubik, P; Hattendorf, B; Guenther, D (2009)
We present the first comprehensive set of dissolved 10Be and 9Be concentrations in surface waters and vertical profiles of all major sub-basins of the Arctic Ocean, which are complemented by data from the major Arctic rivers Mackenzie, Lena, Yenisey and Ob. The results show that 10Be and 9Be concentrations in waters below 150 m depth are low and only vary within a factor of 2 throughout the Arctic Basin (350-750 atoms/g and 9-15 pmol/kg, respectively). In marked contrast, Be isotope compositions in the upper 150 m are highly variable and show systematic variations. Cosmogenic 10Be concentrations range from 150 to 1000 atoms/g and concentrations of terrigenous 9Be range from 7 to 65 pmol/kg, resulting in 10Be/9Be ratios (atom/atom) between 0.5 and 14 × 10-8. Inflowing Atlantic water masses in the Eurasian Basin are characterized by a 10Be/9Be signature of 7 × 10-8. The inflow of Pacific water masses across the Bering Strait is characterized by lower ratios of 2-3 × 10-8, which can be traced into the central Arctic Ocean, possibly as far as the Fram Strait. A comparison of the high dissolved surface 10Be and 9Be concentrations (corresponding to low 10Be/9Be signatures of ∼2 × 10-8) in the Eurasian Basin with hydrographic parameters and river data documents efficient and rapid transport of Be with Siberian river waters across the Siberian Arctic shelves into the central Arctic Basin, although significant loss and exchange of Be on the shelves occurs. In contrast, fresh surface waters from the Canada Basin also show high cosmogenic 10Be contents, but are not enriched in terrigenous 9Be (resulting in high 10Be/9Be signatures of up to 14 × 10-8). This is explained by a combination of efficient scavenging of Be in the Mackenzie River estuary and the shelves and additional supply of cosmogenic 10Be via atmospheric fallout and melting of old sea ice. The residence time of Be in the deep Arctic Ocean estimated from our data is 800 years and thus similar to the average Be residence time in the global ocean. © 2009 Elsevier Ltd. All rights reserved.